Tibial stress fracture after computer-navigated total knee arthroplasty - Massai, F. (Springer International Publishing, 2010)
A correct alignment of the tibial and femoral component is one of the most important factors determining favourable long-term results of a total knee arthroplasty (TKA). The accuracy provided by the use of the computer navigation systems has been widely described in the literature so that their use has become increasingly popular in recent years; however, unpredictable complications, such as displaced or stress femoral or tibial fractures, have been reported to occur a few weeks after the operation. We present a case of a stress tibial fracture that occurred after a TKA performed with the use of a computer navigation system. The stress fracture, which eventually healed without further complications, occurred at one of the pinhole sites used for the placement of the tibial trackers.